Natural products modulate programmed cell death signaling mechanism for treating endometriosis: a review - Zhao, Zhen; Liu, Fangyuan; Yu, Yang; Shen, Ying; Ding, Danni; Han, Fengjuan (Frontiers in Pharmacology, 2026)
Endometriosis (EMs) is a gynecological inflammatory disease that depends on estrogen. Its chief symptoms include dysmenorrhea, chronic pelvic pain, reduced fertility, and pelvic masses. Although various hormonal therapies and surgical treatments are available, their long-term effectiveness is limited, recurrence rates are high, and side effects are significant. Programmed cell death (PCD) is a genetically regulated mechanism of cell clearance that includes apoptosis, autophagy, ferroptosis, pyroptosis, and necroptosis. Numerous studies showed that dysregulation of PCD is strongly associated with the development of EMs, suggesting that targeting key molecular mechanisms of PCD could be a promising therapeutic strategy. Natural products, known for their multitarget activity and low toxicity, show unique advantages in modulating PCD in EMs. This review elucidates the regulatory mechanisms of various PCD pathways in EMs and their interactions with key signaling cascades, including PI3K/Akt/mTOR, MAPK, NF-κB, and Bcl-2. Furthermore, it explores how natural products modulate these PCD mechanisms and related pathways, providing insights into their therapeutic potential at the molecular level. We used “endometriosis,” “programmed cell death,” “natural products”, and “signaling pathway” as keywords to systematically search the PubMed, Web of Science, and CNKI databases for relevant literature published in the past 10 years. A total of 55 studies were included, highlighting recent advances in regulating EMs progression through PCD modulation by natural products. The goal of this review is to provide a theoretical foundation for improving current treatments for EMs and to offer practical recommendations for future research.